PENGARUH PROMOSI ONLINE TERHADAP PENINGKATAN MINAT PENGUNJUNG DI PARIWISATA PUSAT PELATIHAN GAJAH DI DESA SUKA BARU KECAMATAN MARGA SAKTI SEBELAT - Pipit Sumiati; Onsardi Onsardi (Yayasan Insani Mandiri Santani, 2025)
This study aims to examine the influence of online promotion on the increase in visitor interest at the Elephant Training Center in Suka Baru Village, Marga Sakti Sebelat District. The research was conducted from September 2024 to January 2025. The sample for this research is the interest of visitors at the Elephant Tourism Center in Suka Baru Village, Marga Sakti Sebelat District. This research used quantitative methods on 80 respondents. The sampling technique is probability sampling. The method used in this research is a quantitative method with simple regression analysis using SPSS 24 for windows. The research results and hypotheses in this study show that the online promotion variable has a partial positive effect on visitor interest at the Elephant Tourism Training Center in Suka Baru Village, Marga Sakti Sebelat District. Keywords: Online Promotion, Increasing Visitor Interest